Compact efficient polarizers for relativistic electron beams - Kun Xue; Yue Cao; Feng Wan; Zhong-Peng Li; Qian Zhao; Si-Man Liu; Xin-Yu Liu; Li-Xiang Hu; Yong-Tao Zhao; Zhong-Feng Xu; Yousef I. Salamin; Tong-Pu Yu; et al. (Physical Review Research)
Relativistic spin-polarized electron beams are important for fundamental research and the industry, but their generation currently requires conventional accelerators or ultrastrong laser facilities, limiting their accessibility and broad applications. Here, we put forward a method for constructing a compact efficient “polarizer” that achieves direct ultrafast conversion of relativistic dense electron beams into polarized ones, based on a beam “self-polarization” mechanism via beam-target interactions. In this scheme, as the electron beam grazes through the polarizer (a double-layer solid target), it ionizes the target and excites an asymmetric plasma field due to the plasma backflows. This field then reacts on the beam itself, triggering spontaneous radiative polarization and reflecting approximately 10% of the beam, and thereby yielding a dense polarized electron beam. Moreover, the double-layer target setup enhances the plasma field and induces a plasma bubble that focuses the polarized beam and reshapes its polarization distribution. Our method is robust with respect to the beam and target parameters, and opens an avenue for relativistic beam polarization with compact accessible devices, which would facilitate their broad applications and the development of related polarized beam experiments.